Ethanolic extract of Actinidia chinensis var. delicious fruit ameliorates scopolamine-induced cognitive impairment in rats - Shireen Ansari; Sushmita Uniyal; Ayushi Khali; Rishabh Gaur; Karabi Kalita (Pharmacological Research - Modern Chinese Medicine, 2024)
Aim: The present study was to assess the anti-amnesic effect of Actinidia chinensis var deliciosa in a rat model of scopolamine-induced amnesia. Method: 36 rats were divided into 6 groups and assigned name to each group i.e. Group 1 rats (normal control) received 1 ml/kg normal saline for 14 days intraperitoneally (i.p.). Group 2 rats received scopolamine (3 mg/kg, i.p.) 30 min prior to the trial on the 14th day. Group 3 rats received 3 mg/kg/day of donepezil as pre-treatment for 14 days and scopolamine (3 mg/kg, i.p.) 30 min before the trial on the 14th day. Group 4, 5, and 6 rats received Actinidia chinensis var deliciosa (200, 400, and 600 mg/kg/day) for 14 days and scopolamine (3 mg/kg, i.p) 30 min before the trial on the 14th day respectively. On day 15, 6 rats from each group were sacrificed and the brain tissue of these rats was isolated for the estimation of biochemical parameters, and histopathological examination. Result: Scopolamine-treated rats demonstrated increased escape latency and lipid peroxidation levels in the hippocampus compared to the control group (p < 0.001). However, pre-treatment with Actinidia chinensis var deliciosa extract (ACEE) at various doses and the standard drug donepezil significantly improved these parameters. Histopathological examination revealed that ACEE and donepezil protected against pyramidal cell degeneration, neuronophagia, and vascular inflammation in scopolamine-treated rats. Discussion: Actinidia chinensis var deliciosa showed promising anti-amnesic activity against scopolamine-induced amnesia in rats. This could be attributed to its brain acetylcholinesterase level and alteration in neurotransmitter level.